'Just Knowledge': Can Social Work's 'Guilty Knowledge' Help Build a More Inclusive Knowledge Society?. (15th December 2018) - Heinsch, Milena; Cribb, Alan
Abstract: In contemporary societies, the value and importance of knowledge is increasingly tied to its potential to generate profit. This raises questions about whether and how knowledge can, at the same time, be harnessed and valued for its capacity to advance social justice. In this paper, we consider these questions in relation to social work knowledge and academic research utilisation, setting our analysis in the context of broader debates on these themes. As well as highlighting the risks that the 'knowledge economy' poses to certain currents of knowledge (currents within social work and analogous currents in other fields), we ask what might be done to protect and realise the value of these currents. We suggest that the example of social work usefully illuminates both the potential and challenges of knowledge utilisation for social justice more broadly.